Optimal process design for integrated municipal waste management with energy recovery in Argentina. (February 2020) - Morero, Betzabet; Montagna, Agustín F.; Campanella, Enrique A.; Cafaro, Diego C.
Abstract: This work presents a comprehensive mathematical model for the optimal selection of municipal waste treatment alternatives, accounting for co-digestion of sludge and municipal solid waste. The superstructure of alternatives includes anaerobic digestion under mesophilic or thermophilic conditions, composting, recycling, and final disposal in a landfill. Anaerobic digesters can be fed with different mixing ratios of sewage sludge (SS) and the organic fraction of municipal solid waste (OF). A mixed-integer mathematical programming formulation is proposed to find the optimal process design. It comprises nonlinear equations to estimate digestion yields according to substrate mixing ratios. Results for cities of different sizes show that the joint treatment can increase profitability, especially in small populations. In all cases, co-digestion of the full stream of SS and OF leads to an integrated waste-to-energy process that maximizes the economic value and reduces environmental impacts of waste by producing electricity, heat and fertilizer. Highlights: Different alternatives for integrated urban waste treatment are evaluated. A mathematical formulation to find the optimal process design is developed. Joint treatment of wastes can increase profitability, particularly in small cities. The optimization model accurately assesses the economies of scale of the treatment.